Big data for smallholders - Mohamed Shariff, Abdul Rashid (Institute of Plantation Studies, Universiti Putra Malaysia, 2017)
This paper provides an insight into how big data can be applied for smallholders in the settings of developing or underdeveloped country. It begins by giving an introduction on big data and shows how big data can be utilized. Specific examples on how big data can be used to help smallholders are provided, particularly relating to paddy and oil palm. Some recommendations for future applications are provided at the end of the paper.